2005
DOI: 10.1186/1743-7075-2-24
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of RANKL is Increased and OPG Decreased During Dietary Magnesium Deficiency in the Rat

Abstract: Background: Epidemiological studies have linked low dietary magnesium (Mg) to low bone mineral density and osteoporosis. Mg deficiency in animal models has demonstrated a reduction in bone mass and increase in skeletal fragility. One major mechanism appears to be an increase in osteoclast number and bone resorption. The final pathway of osteoclastogenesis involves three constituents of a cytokine system: receptor activator of nuclear factor kB ligand (RANKL); its receptor, receptor activator of nuclear factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 23 publications
1
5
0
1
Order By: Relevance
“…On the one hand, magnesium availability is important for bone formation, and it was found that magnesium deficiency causes OPG/RANKL ratios that promotes osteoclastogenesis (in osteoblasts, up to 16-fold after a 50% magnesium nutrition diet for 6 months compared with the control). 37 On the other hand, magnesium supplementation increases serum OPG and leads to variations in the OPG and RANKL presence, which seems to favor bone formation. 38 In our case, the OPG/RANKL ratios are heterogenic ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, magnesium availability is important for bone formation, and it was found that magnesium deficiency causes OPG/RANKL ratios that promotes osteoclastogenesis (in osteoblasts, up to 16-fold after a 50% magnesium nutrition diet for 6 months compared with the control). 37 On the other hand, magnesium supplementation increases serum OPG and leads to variations in the OPG and RANKL presence, which seems to favor bone formation. 38 In our case, the OPG/RANKL ratios are heterogenic ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…A third outcome that does not match those present in the literature is the number of osteoclasts calculated in the femoral and tibial metaphyses; in fact, the NOc/BS remains the same independently of the treatment ( Table 4 ). Indeed, it is reported that rats fed a Mg-deprived diet [ 13 , 15 , 18 , 19 ] or diets at 10% of the Mg nutritional requirement [ 12 ] show in the trabecular bone an increase in the osteoclast number and in the surface covered by osteoclasts, suggesting that the decrease in bone mass is due to an increase in bone resorption. In consideration of the above-discussed findings, it is remarkable to highlight that the results obtained in rats cannot be directly compared with those obtained with mice since these two species show genetic and metabolic differences, and it is not possible to establish reliable general rules to validate extrapolation from one species to another [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several experimental studies in rodents have shown that progressively reduced Mg diets, compared with the recommended daily intake, result in a corresponding loss of bone mass and increased skeletal fragility, due to increased bone resorption and/or reduced bone formation during skeletal remodeling [ 10 , 11 , 12 , 13 , 14 , 15 ]. In fact, Mg has been shown to be important for bone cell activity: (i) in vitro its depletion causes inhibition of osteoblastic growth, while its presence has a mitogenic action [ 16 , 17 ]; (ii) in vivo, its depletion causes both a decrease in the number of osteoblasts associated with alteration of their function and an increase in the number of osteoclasts and the surfaces eroded by them [ 11 , 12 , 13 , 18 , 19 ]. In addition, magnesium deficiency increases the production of pro-inflammatory cytokines, such as tumour necrosis factor-α ( TNF-α ), interleukin-1 ( IL-1 ), and substance P , which promote bone resorption by osteoclasts [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reduction in dietary Mg by 25% in rats resulted in lower trabecular thickness and reduced bone volume, which may be associated with inflammation-associated activation of osteoclastic bone resorption [ 59 ]. The up-regulation of RANKL expression along with the down-regulation of OPG expression was considered a key mechanism linking bone resorption and Mg deficiency [ 60 ]. Yet, despite a significant increase in osteoclastogenesis upon Mg deficiency, the resorptive activity of these cells was reduced [ 61 ].…”
Section: Magnesium (Mg)mentioning
confidence: 99%